Classroom Management Strategies in Elementary Schools - Aliyyah, Rusi Rusmiati; Febriani, Alia (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research aims to describe effective classroom management strategies in Elementary Schools (SD) and analyze the urgency of Implementation, benefits, and challenges. The research approach uses a quasi-qualitative design with a Simple Research Design (SRD) and involves 13 elementary school teachers in West Java as respondents. Data were collected through interviews and analyzed using NVivo 12 software-assisted thematic techniques. The study results show that classroom management is essential in character building, creating a conducive learning environment, and supporting students’ social-emotional development. Teachers implement strategies that include drafting clear classroom rules, building positive student relationships, attractively arranging classrooms, providing positive reinforcement, and conducting evaluations and reflections. Effective classroom management has been shown to provide various benefits, such as improving student focus, motivation, discipline, and learning outcomes, and strengthening social relationships. Despite this, teachers face multiple challenges, such as the diversity of students’ characters, limited resources, and a lack of parental support.